Interferon‐Related Transcriptome Alterations in the Cerebrospinal Fluid Cells of Aicardi‐Goutières Patients - Izzotti, Alberto (Blackwell Publishing Ltd, 2008)

(untitled) (Brain Pathol)
Aicardi–Goutières syndrome (AGS) is a rare interferon (IFN)‐related encephalopathy with onset during the first year of life. AGS, is clinically characterized by progressive microcephaly, bilateral basal ganglia calcification, cerebral atrophy, cerebrospinal fluid (CSF), lymphocytosis, delayed development of psychomotor abilities with pyramidal–extrapyramidal syndrome and mimics congenital viral infections. Microarray analysis examining the expression of 18 880 human genes has been applied to the CSF lymphocytes of 20 AGS cases (age 4.5 ± 4.4 years, mean ± standard deviation) characterized by high IFN‐alpha levels in CSF and 20 matched controls (age 4.4 ± 4.3 years, mean ± standard deviation). Gene‐expression data reveal significant differences between AGS cases and controls for all controls and 18 AGS cases. The two AGS cases unclassified as compared with controls were both older than 7 years. AGS cases presented upregulation of genes involved in IFN‐dependent pathways and lymphocyte functions, paralleled by the downregulation of genes encoding for angiopoietic activities. The cystatin F and DNAJ genes, having a negative feedback on IFN pathways, underwent a progressive age‐related increase in their expression. These gene‐expression signature parallels a progressive attenuation of clinical symptoms with age. Obtained results provide evidence that exposure to IFN‐alpha is harmful for developing brain.